An exploratory study on the perceived challenges, coping strategies and facilitating factors for optimal implementation of community-based mental health services in Malaysia: a study protocol - Almi, Ahmad Anas; Abdul Khaiyom, Jamilah Hanum (Malaysian Psychiatry Association, 2020)
Introduction: The present study aims to explore the perceived challenges, coping strategies, and facilitating factors for optimal implementation of community-based mental health services (CMHS) as the system of care for community mental health institutions (CMHI). The literature review has suggested that the aspects of barriers and facilitators are leading to the factors associated with the service provider, patient, provided treatment, and the healthcare system. However, there is a lack of centralised information about the current implementation of CMHS in Malaysia. The lack of readily- available information on the efficacy of CMHS as the system of care has led to this current inquiry. The study aims to explore on-the-ground experiences of the optimal implementation of CMHS in the CMHI in Malaysia through the perspective of mental healthcare professionals. Methods: This intended research will employ a qualitative approach and data will be collected through semi-structured in-depth interviews. Samples of the study will be recruited from in-service healthcare professionals attached to CMHI including psychiatrists, clinical psychologists, counsellors, occupational therapists, physiotherapists, nurses, and other related personnel. This study requires the respondents to give their opinions towards a set of interview questions that will consist of three (3) main questions. It is expected that each interview session takes about 40 minutes to 1 hour 30 minutes. Later, the interview transcripts will be analysed using the thematic analysis method. Expected results: The study is hoped to explore the experiences of in-service mental healthcare professionals in the CMHI and attempts to identify, describe, and investigate the components of perceived challenges, coping strategies, and facilitating factors towards the optimal implementation of CMHS through their point of view. Conclusion: It is vital to understand the perceived challenges, coping strategies, and facilitating factors towards the implementation of optimal CMHS to contribute to better planning and policy development vis-a-vis in the delivery of optimal services to the deserving community.